EXPRESSIVENESS OF NEGATIVE CONSTRUCTIONS IN AGATHA CHRISTIE’S NOVEL “THE PALE HORSE” - Myroslava I. Venhryniuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
This article deals with the expressive potential of negative constructions in the literary text belonging to the detective genre. The material of Agatha Christie’s novel “The Pale Horse” proves that negative constructions are part of a range of powerful means of expression and perform a number of functions. Denial constructions contribute to the deepening of the emotionality and value of the artistic text, promotes its dialogic progression, takes an active part in the expressive labeling of communicative acts, dynamizes the speech interaction of the characters. The article uses the following research methods: descriptive, which revealed the features of the expressive potential of negative constructions in a detective fiction, and methods of contextual and oppositional analysis, which were aimed at role revealing of negative constructions in the formation of value and emotion in the text. It has been found that in a detective fiction, such categories as denial and emotion are closely interconnected. The emotional tension created by means of negation promotes strengthening of text dynamics, expression of plot collisions, activation of reader’s attention. The reader, being immersed in the emotional states of the characters, lives with them their anxiety, worry, fear, pain, frustration, excitement. As a result, the text resonator strains, the communicative distance between the character, the author and the reader decreases, the effect of everyone’s involvement in the disclosure of the crime is created. In particular, in Agatha Christie’s novel “The Pale Horse”, we come across an expression of a rich range of characters’ emotions: compassion, irritation, fear, doubt, hatred, despair, and so on. The article notes that the expressive potential of negative constructions is fully revealed when it comes to the evaluative attitude of the character to other characters, events, phenomena and so on. The article emphasizes that the assessment is in constant dynamics, changing, as this is facilitated by the very nature of the detective genre. It is established that negative constructions take an active part in the expressive marking of communicative acts of an artistic text. In a detective fiction, the following are most often expressively marked: suspicion, conjecture, assumption, distrust, reproach, order, assurance, accusation. It is noticeable that the negative constructions, coloring the communicative acts of the characters with expressive shades, can promote, on the one hand, the progression of the dialogues of the literary text, on the other – to signal their collapse. The article pays special attention to such communicative acts as conjectures and assumptions. It has been found that by building a confusing chain of conjectures and assumptions, the author enhances the reader’s curiosity, stimulates detective searches, emphasizes the dynamics of crime detection. It emphasizes that the negative constructions help emphasize a certain feature of the character’s appearance, the specifics of his behavior and character traits. Denial construction is able to express and crystallize the image, give it individuality, brightness and clear delineation. Against the background of the general artistic picture of the work, the negation allows to make the image of the character recognizable and noticeable, emphasizing some unique feature of the character or giving it an image of comic color